2012
DOI: 10.1007/s00256-012-1451-0
|View full text |Cite
|
Sign up to set email alerts
|

Explorative study of the sensitivity and specificity of the pronator quadratus fat pad sign as a predictor of subtle wrist fractures

Abstract: ObjectiveTo investigate the value of post-traumatic pronator quadratus (PQ) fat pad sign as a reliable predictor of subtle wrist fractures.Materials and methodsThis was a prospective study of 68 patients undergoing X-ray for traumatic wrist injuries and subsequent MRI. The reliability of a positive PQ fat pad sign on X-ray, defined as either raised, interrupted or obliterated, was evaluated in detection of subtle wrist fractures.ResultsOut of 68 patients, 28 had a positive PQ sign without any obvious bony inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Mac Ewan was first to characterize the pronator quadratus fat pad sign consisting of a radiolucent (fat containing) stripe which runs parallel to the pronator quadratus muscle covering the distal radius and ulnar (Figure 1 )[ 1 , 2 ]. Studies on healthy subjects have shown that thickness of the pronator quadratus complex (PQC) is significantly greater in men (values up to 9 mm) than in women (values up to 8 mm) and increases with age[ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mac Ewan was first to characterize the pronator quadratus fat pad sign consisting of a radiolucent (fat containing) stripe which runs parallel to the pronator quadratus muscle covering the distal radius and ulnar (Figure 1 )[ 1 , 2 ]. Studies on healthy subjects have shown that thickness of the pronator quadratus complex (PQC) is significantly greater in men (values up to 9 mm) than in women (values up to 8 mm) and increases with age[ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the past several studies have analyzed the usefulness of the PQS to detect subtle fractures or inflammation of adjacent e in their detecting[ 7 ]. Sensitivity of the PQS measured on lateral X-rays to detect occustructures[ 3 , 4 , 5 , 7 ]. While earlier studies described the PQS as a useful adjunctive to detect subtle fractures[ 1 ], more recent studies, which used MRI as a reference, have found this sign to be unreliabllt distal forearm fractures has been reported to range between 26% and 65%.…”
Section: Introductionmentioning
confidence: 99%
“…During the fracture repair through a volar approach, the pronator quadratus (PQ) muscle is stripped off the radius in order to apply the volar plate 3). However, it is generally difficult to repair the PQ muscle at the end of the operation, because the muscle fascia is not strong enough to hold sutures,4,5,6) and the muscle can also be injured due to the fracture 7,8). However, a recent study evaluated the integrity of the PQ muscle repair radiographically by using radiopaque hemoclips, and it reported that PQ repairs are generally durable 9)…”
mentioning
confidence: 99%
“…In patients with distal forearm fractures, blood may displace the fat plane anteriorly and create the pronator quadratus fat pad sign (figure 1). 1 False-negatives occur if radiographs are poor quality or obtained before blood can accumulate, or if fractures are not under the pronator quadratus muscle. False-positives occur in some arthritides, infections and soft tissue injuries.…”
mentioning
confidence: 99%
“…Sensitivity and specificity of the sign are 26–65% and 70%, respectively 1 2. Patients with a positive fat pad sign but otherwise normal radiographs may require additional imaging to assess for fracture.…”
mentioning
confidence: 99%